Geographic Information System (GIS) for Optimizing Hospital Distribution and Accessibility in Padang City, Indonesia - Andri Candra; Deval gusrion (Jurnal Ilmu Komputer dan Informatika | E-ISSN : 3063-9026, 2025)
This study aims to map the locations of hospitals in Padang City using Geographic Information Systems (GIS) to improve accessibility and efficiency in the distribution of healthcare services. The mapping also aims to provide a clearer overview of the hospital distribution across the city, assisting the government in planning more equitable healthcare facilities. Data used in this study was obtained from available hospital databases and geographic coordinates recorded using a web-based GIS system. The mapping results show a concentration of hospitals in the city center, while the outskirts of Padang City still lack healthcare facilities. This mapping allows the public to easily access information on nearby hospital locations, while enabling the government to plan the construction of new hospitals in more strategic areas. This study also recommends integrating this GIS mapping with other health information systems to enhance decision-making in the healthcare sector.